Experimental studies of furfural production from water hyacinth (Eichhornia Crassipes) - Wijittra Poomsawat; George Tsalidis; Christos Tsekos; Wiebren deJong (Energy Science & Engineering, 2019)
Abstract Furfural is a very promising product of lignocellulosic biomass‐based biorefineries and has the potential to become a useful resource for further conversion and utilization. Aquatic plants show an enormous potential as feedstock since they do not compete for land use, and they require minimal water consumption in a biorefinery concept due to their very high water content. This work is focused on experimental studies of furfural production from water hyacinth (Eichhornia crassipes) by means of aqueous, acid‐catalyzed dehydration. The temperature range of the process, and the acid and seawater presence were chosen based on the previous relevant studies. The aim of the study was to determine whether water hyacinth is suitable for furfural production. The experiments were performed between 160°C and 200°C with a water hyacinth concentration of 2 wt%. The results suggest that the effects of acid catalyst presence on biomass dehydration are similar to the case of pure pentose dehydration. Furthermore, the addition of seawater did not have a positive catalytic effect in terms of the furfural yield. The maximum yield was 53.2 mol% based on the C5 sugar content in the original biomass. The furfural yield of 7.9 wt% of water hyacinth input was comparable to the yield of feedstocks such as corn cob, bagasse, and oat's residue and higher than the cases of rice straw or hulls. Thanks to the comparatively high pentose potential, water hyacinth shows promising results as a candidate feedstock for furfural production. A certain variability of pentosan should be taken into account, as the chemical composition of the plant depends on the source and harvesting seasons.